2012
DOI: 10.2174/138945012798868470
|View full text |Cite
|
Sign up to set email alerts
|

The Other Side of Opioid Receptor Signalling: Regulation by Protein-Protein Interaction

Abstract: Opiate drugs mediate their analgesic, euphoriant, and rewarding effects by activating opioid receptors. Pharmacological and molecular studies have demonstrated the existence of three opioid receptor subtypes, μ, δ, and κ- that couple predominantly to Gi/Go types of G proteins to regulate the activity of a diverse array of effector systems. Ample experimental evidence has demonstrated that these receptors can physically interact with a variety of accessory proteins, confirming that signal transduction of the op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 271 publications
1
27
0
2
Order By: Relevance
“…all three OR subtypes (Fig. 1A) and forms helix VIII, which is proposed to 551 be the docking site of RGS4, spinophilin, periplakin, GASP and the tran-552 scription factors STAT5A/5B among others [13]. The present data indi-…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…all three OR subtypes (Fig. 1A) and forms helix VIII, which is proposed to 551 be the docking site of RGS4, spinophilin, periplakin, GASP and the tran-552 scription factors STAT5A/5B among others [13]. The present data indi-…”
mentioning
confidence: 60%
“…κ-OR couples to PTX sensitive G proteins and has 517 the ability to interact also with various other proteins, involved in the 518 signalling, trafficking, intracellular sorting and fine tuning of this recep-519 tor [13,40]. CT and the δ-i3L indicated the ability of RGS4 to interact with μ-OR 526 and δ-OR, to modulate OR signalling [12,20].…”
mentioning
confidence: 99%
“…It could involve facilitation of recruitment of any of the many proteins that have been shown to interact directly with MOPr (Georgoussi et al, 2012).…”
Section: Tsstmentioning
confidence: 99%
“…Chu et al (2010) reported that morphine-induced, PKC-mediated desensitization is mediated partly by phosphorylation of Ga i2 subunits, which should be independent of C-terminal phosphorylation. It is possible that PKC-dependent phosphorylation of residues in the intracellular loops (Williams et al, 2013) or in other interacting proteins (Georgoussi et al, 2012) contribute to morphineinduced desensitization. Complex PKC-dependent mechanisms must contribute because calphostin C inhibited by approximately 50% in wild-type MOPr but completely abolished it in 11S/T-A.…”
Section: Tsstmentioning
confidence: 99%
“…G protein-coupled receptors can engage multiple signaling pathways through their interactions with β-arrestins and a host of other proteins in addition to G proteins. 3235 Moreover, different ligands acting at the same receptor can engage different subcellular signaling pathways (i.e. ligand-biased signaling).…”
Section: Discussionmentioning
confidence: 99%